Acquired Surface Alexia in Spanish: A Case Report - Aldo R. Ferreres; Macarena Martinez Cuitiño; Alicia Olmedo (Behavioural Neurology)
This paper reports a case study of acquired surface alexia in Spanish and discusses the most suitable tests to detect this syndrome in a writing system that is very regular for reading at the segmental and supra-segmental levels. Patient MM has surface alexia characterized by quantitatively good performance in reading words and pseudowords; accurate but slow and syllabic reading of words, nonwords and sentences; good performance in lexical decision tasks including words and nonwords; errors in lexical decision with pseudohomophones; and homophone confusions. This pattern of reading can be interpreted as a disorder in the lexical reading route and overdependence on the non-lexical route. We discuss nonlexical impairments and the interpretation of alexia and suggest tasks to identify surface alexia in a shallow orthography.